Strategi kesiapsiagaaan menghadapi bencana di Perpustakaan UIN Mahmud Yunus Batusangkar - Wahyuni, Sri; Manita, Rika Jufriazia (Daluang: Journal of Library and Information Science, 2024)
Purpose. This study aims to determine the disaster preparedness carried out by the UIN Mahmud Yunus Batusangkar Library in disaster prevention. It is hoped that this study will be an important contribution to institutions regarding the need for a standard on disaster preparedness. Methodology. The methods used in this research use qualitative methods. In data collection researchers use direct observation techniques, semi-structured interviews, and documentation. Results and discussion. The preventive measures that the library has undertaken by organizing, training, and simulating disasters are usually held by the university every year and are dedicated only to K3 officers. In addition, the library's cooperation with local cooperating with the firefighters. Responsive action makes plans and rescue efforts collections at the UIN Mahmud Yunus Batusangkar Library, training, and disaster simulations are usually held by the university every year to occupational safety and health team. The repairs in 2009 in West Sumatra were devastated by an earthquake and caused the walls of the library to crack and the ceilings of the libraries to fall onto the shelves, as well as causing a lot of dust to burst into the books. To anticipate that, the library did a fumigation. Conclusions. Overall, the library has planned optimal disaster preparedness, which is sourced from the provision of equipment and work safety training in dealing with disasters. As a recommendation from the author, it is expected to provide disaster response training for library managers so that they can respond quickly when a disaster occurs.